Sjögren's syndrome: current knowledge and future prospects - Tzioufas, Athanasios G. (Henry Stewart Talks, 2018)
Introduction to Sjögren's syndrome, Humoral and cellular autoimmune responses in Sjögren's syndrome, Description of heterogenic clinical features of disease, Pathogenetic/immunopathologic aspects and associations with clinical phenotypes, The need for precise therapeutic approaches, Development and features of lymphoma in Sjögren's syndrome, Risk factors for development of severe disease, Biomarkers for disease severity, outcome and lymphoma